Arterial stiffness and shortened QTc interval are associated with androgen and ACTH levels in classic congenital adrenal hyperplasia - Campioni, Lorenzo; Di Carlo, Maria Chiara; Sola, Chiara; Bergoglio, Beatrice; Bollati, Martina; Montesano, Giulia; Ponzetto, Federico; Lopez, Chiara; Motta, Giovanna; Parasiliti-Caprino, Mirko; Giordano, Roberta (Frontiers in Endocrinology, 2025)
ContextCardiometabolic complications are increasingly recognized in congenital adrenal hyperplasia (CAH) due to 21β-hydroxylase deficiency, but adult data remain limited.ObjectiveTo evaluate cardiovascular and metabolic alterations in adult patients with classic CAH under glucocorticoid treatment, compared to matched controls.MethodsA cross-sectional study was conducted on adults with classic CAH and sex- and BMI-matched controls. Cardiovascular and metabolic variables and parameters were collected in all patients.ResultsThe study enrolled 32 CAH patients and 73 controls. In univariate analyses, CAH patients showed significantly shorter QTc intervals (p=0.004), longer QRS duration and shorter RR intervals, in comparison with controls. Even in presence of a more favorable hypertensive (lower diastolic blood pressure and higher heart rate variability) and metabolic profile (lower fasting glucose, LDL cholesterol, triglycerides, and higher HDL), CAH patients had higher Ambulatory Arterial Stiffness Index (AASI) (p=0.006). Multivariate regression confirmed the association between CAH and both increased AASI (EC 1.131, p<0.001) and shortened QTc (EC 0.977, p=0.039), adjusting for all potential confounders. Within the CAH group, 17-hydroxyprogesterone was positively associated with AASI (EC 1.001, p=0.049), while ACTH (EC 0.999, p=0.021) was inversely associated with QTc, after correction for all clinical confounders. Propensity score-matched analysis with 1:2 matching ratio, based on the same regression models, confirmed that CAH diagnosis was associated with AASI (p<0.001) and QTc (p=0.004).ConclusionsAdults with classic CAH show increased arterial stiffness and altered cardiac repolarization, likely linked to chronic hormonal imbalance. These findings underscore the need for cardiovascular monitoring in long-term CAH management.